CLINICAL AND MEDICO-LEGAL CONSIDERATIONS ON THE VICINITY OF THE THIRD MOLAR WITH THE MANDIBULAR CANAL - LITERATURE REVIEW - Simona Andreea Moraru; Romică Cergan; Elena Nicoleta Bordea; Angelo Pellegrini; Ramona Ionela Truţă; Suzana Carmen Cismaş; Vanda Roxana Nimigean; Natalia Motaş; Victor Nimigean (Romanian Society of Oral Rehabilitation, 2021)
The mandibular third molar has variable root morphology. Moreover, it quite often presents eruption disturbances, such as partial or total impaction. The mandibular third molar lies in the vicinity of the mandibular canal and its neurovascular content. The mandibular canal has often close or tangent relationship with the root apices and even with the crown of this tooth, in the case of its deep impactions. Such aspects become favourable factors for neurovascular complications following various radical or conservative treatments performed on these teeth, taking into account the fact that these therapeutic procedures are frequent in dentistry. The current study presents the consequent complications of endodontic and surgical treatments at the level of the mandibular third molar as well as their clinical and medico-legal implications, aiming at focusing dentists' attention on correct diagnosis and management.